Solid Polymer Blend Electrolyte Based on Poly(ethylene oxide) and Poly(vinyl pyrrolidone) for Lithium Secondary Batteries - K. Kesavan (Brazilian Journal of Physics, 2015)
Solid polymer electrolytes have attracted con- siderable attention due to their wide variety of electro- chemical device applications. In the present study, the fixed concentration of the salt lithium perchlorate (LiClO 4 ) and various concentrations of poly(ethylene oxide)/poly(vinyl pyrrolidone) (PEO/PVP)-based electro- lytes were prepared by solvent casting technique. The structural analysis of the present system shows that the amorphous character of the samples is responsible for the process of ion transport. Fourier transform infrared spectroscopy (FTIR) has been used to characterize the structure of polymer and confirm the complexation between the polymers and salt. The maximum ionic con- ductivity value is found to be 0.2307×10 − 5 Scm − 1 for PEO (90 wt%)/PVP (10 wt%)/LiClO 4 (8 wt%) (A1) complex at 303 K (30 °C).